Staff competencies as predictors of work engagement : a case study on administrative staff at Fatoni University Thailand - Nawae, Yihan (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The main purpose of the study is to examine the staff competencies as predictors of work engagement among the administrative staff at Fatoni University, Thailand. The study used the Tucker and Cofsky theory to investigate the factors. The theory introduces six variables in predicting work engagement i.e. skill, knowledge, self-concept, trait, and motive. The study also investigates the level of administrators' work engagement as explained by the perceived competency. In addition, the study also ascertains if there are any relationship between perceived competencies and work engagement. The sample consist of 155 the respondent in administrative staff Fatoni University. Two questionnaires used to be an instrument in order to collect data from the sample. The first is "General Staff Competencies Questionnaire" and the last one is "Work Engagement Questionnaire ". The statistical include of descriptive statistics, correlation analysis, and multiple regression analysis. The finding show that the competencies on five dimensions of administrative staff skill, knowledge, self-concept, trait, and motive are practiced by them at a middle level as the overall performance and as individual factors ranged from the most to the least average which were motive, self-concept, trait, knowledge, and skill respectively. As well as work engagement was found at a moderate level as the overall performance. In addition, staff competencies of Fatoni University reflected significant relationship with all of the key processes except the dimension of self-concept which was found significant different.